To study the variation in epidemiology, clinical, and laboratory profile of scrub typhus patients in COVID-19 and post-COVID-19 era in a tertiary care hospital, Jaipur - Shaveta Kataria; Chinkle Sharma; Trimaan Kaur Bains; Yogita Jangid; Mohit Kumar (Muller Journal of Medical Sciences and Research)
Background: Scrub typhus is an infective disease caused by Orientia tsutsugamushi, which is transmitted to humans by chiggers. Although scrub typhus is a public health threat, distribution remains unclear due to the scarcity of data and appropriate surveillance systems. An early diagnosis and institution of specific treatment will help to reduce morbidity and mortality due to scrub typhus. Study Design: This was a retrospective descriptive study. Materials and Methods: This is the study with duration of 3 years and 9 months. The details were collected from the patients who presented with acute undifferentiated febrile illness and whose immunoglobulin M was positive with enzyme-linked immunosorbent assay for scrub typhus and entered into the Excel sheet, and the analysis was done. Results: Three thousand and six hundred and thirty-three samples were received with the maximum number of positive cases reported in the age group of 15–25 years in the COVID-19 wave and 26–36 years in post-COVID-19 (P < 0.001). The maximum number of positive cases has been reported in females and predominantly reported in September. Among positive patients, the most common clinical presentation is fever in post-COVID-19 times with altered laboratory profile. The most common complication was acute respiratory distress syndrome. Hence, less number of cases has been reported in the COVID-19 first wave, followed by the second wave and post-COVID-19 times. Conclusion: Scrub typhus is an acute febrile illness associated with non-specific symptoms, life-threatening complications, and large mortality rate, and even higher number of infected patients have been reported in post-COVID-19 times, this might be due to decrease in the immune status of the population after this pandemic.